The impact of innovation, technology and community factors on innovative services in Dubai police-the moderation role of government intervention - Almazrooei, Khalid Khalifa Fadhel Khalifa (2022)
This research aims to study the impact of innovation and technology (the ability to innovate, use of technology, community cooperation, community communication) on innovative services in light of the mediating effect of government intervention on that relationship in the Dubai Police. The study is quantitative systematic research based on original data collected for the target population of Dubai Police based on a wellstructured survey. The study is an empirical investigation by surveying civil servants in Dubai Police who know a lot about security developments in Dubai based on a predetermined hypothesis. The target group or study group selected for this research work is equivalent to the total number of employees working in Dubai Police who would like to respond to the questionnaire during the data collection period. The actual sample size is 344 employees, and the distributed survey is 534, which was distributed using face-to-face data collection methods in a style suitable for the selected samples in 2021. In general, the statistical results showed satisfactory predictive power and significant predictive significance of the model, the relevant R-squared value of the model was 0.570 (57% power) and the related Q-square is 0.341 (34.1% correlation). The study reached many results, the most important of which is that Dubai Police is proactive in preventing crimes by discovering the latest technologies. Also, the vast majority of innovation applications carried out by Dubai Police effectively meet the needs of society, while modern innovations in Dubai Police contributed to protecting Dubai citizens from domestic and international crimes.